Second opinion opportunity declined: patient typology and experiences regarding the decision-making process preceding elective surgeries in Germany - Susann May; Dunja Bruch; Felix Muehlensiepen; Barbara Prediger; Dawid Pieper; Cecile Ronckers; Sebastian von Peter; Edmund Neugebauer (BMC, 2022)
Abstract Background To address the problem of overuse of elective surgery and to support patients in their decision-making process, a Second Opinion Directive was introduced in Germany, which enables patients with statutory health insurance to obtain a second opinion for certain surgical indications. The study aims to identify, based on the experiences of patients who have undergone elective surgery, the role of seeking a second opinion in reaching their decision. Methods Sixty-two patients who had undergone an elective surgery (hysterectomy, tonsillectomy, shoulder arthroscopy) were recruited using purposive sampling and interviewed during October to December 2020. The transcribed interviews were analysed using a framework analysis to create a typology from the patient's perspective. Results The time spent by patients in making the decision to undergo surgery varies between individuals, and is influenced by factors such as the type of physician-patient relationship, individual patient aspects, prior experiences in the health care system, as well as information needs. Within the framework of the analysis, we were able to identify three patterns of patient types based on the three different time-points or phases when decisions were typically made, with one type being divided into two subtypes: Type 1a: Quick decision making, Type 1b: Overwhelmed quick decision making, Type 2: Time to consider, Type 3: Struggling with the decision. Conclusions Patients who followed a recommendation for elective surgery appreciate having the possibility to seek a second opinion. However, various factors influenced their opting for a second opinion during the decision-making process. Patients have differing information needs, such that a one-size-fits-all second opinion service may not fit adequately for all patients.